Long-term outcomes after revascularization and medical therapy in premature coronary artery disease for cost-effectiveness study: A systematic review protocol - Farbod Ebadi Fard Azar; Ali Aboutorabi; Mohammad Afrouzi; Marjan Hajahmadi; Sanaz Karpasand (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The long-term outcomes are important concepts for cost-effectiveness analysis in patients with premature coronary artery disease after revascularization (coronary artery bypass grafting [CABG] and percutaneous coronary intervention [PCI]) and medical therapy (MT). The finding of this study will be used to calculate the events probabilities for cost-effectiveness study. METHODS AND ANALYSIS: This systematic review will use studies in which patients age must be 18-60 years in eligible studies that obtained from PubMed, Web of Science, Scopus, and Embase. We will assess the long-term outcomes after CABG, PCI, and MT by random-effects meta-analysis and effects will be shown by risk ratio. We will ascertain the probabilities of adverse events during certain periods and then outcomes will compare separately based on specific characteristics. CONCLUSION: This study will provide information related to outcomes of CABG, PCI, and MT in patients with premature coronary artery disease. Doing this systematic review is valuable from clinically and economically aspects such as cost-effectiveness and cost-utility analysis.